Formulation and evaluation of gastro-retentive floating bilayer tablet for the treatment of hypertension - Maddiboyina, Balaji (Heliyon, 2020)
The paper aimed to progress an ideal gastro retentive drug delivery system intended for directing Losartan and Hydrochlorothiazide as a fixed-dose combination for anti-hypertensive therapy. The bilayer tablets were primed through direct compression method. Losartan was formulated by means of a floating layer expending hydrophilic swellable polymer Hydroxy Propyl Methyl Cellulose K4M, ethyl cellulose (4cps) as a buoyancy enhancer, sodium bicarbonate as a gas spawning agent. The amount of polymer blends remains optimized using 2(3) full factorial designs. The clout of experimental factors such as swelling agent concentration, buoyancy enhancer and gas generating agent on floating lag time, total floating time, T50% and % drug release remain investigated to get optimized formulation. The responses remain analyzed using Analysis of variance, and polynomial equation stood created for every retort using Multiple linear regression analysis. Entirely preparations floated for more than 12 h. The release pattern of losartan stood fitted to diverse models based on the coefficient of correlation (r). All the formulations, except F2, showed the Korsemeyer-Peppas model as the best fit model. Formulation F2 showed the zero-order model. Diffusion exponents (n) remained indomitable designed for entirely formulations (0.45–0.89), accordingly the chief drug discharge mechanism was non-fickian (anamolous) transport. Formulation F4 containing 20% w/w Hydroxy Propyl Methyl Cellulose K4M, 15% Sodium bicarbonate and 5% ethyl cellulose (4cps) was the best formulation as per the range of drug release remain institute to be more than 95 % in 12h and floating lag time was 20.15 s. The immediate-release layer stood optimized using crospovidone and Indion 414 as a super disintegrant. Formulation A8 containing 2% Indion 414 was considered as optimized formulation as it released 99% drug within 35 min and possessed less disintegration time. Optimized formulation F4 from the controlled-release layer and A8 from immediate-release layer was used to formulate bilayer tablet. The optimized formulation was imperilled to stability reading for three months at 40(○)C/75% relative humidity. The stability revision exhibited no substantial alteration in the appearance of tablets, floating characteristics, drug content and in-vitro drug dissolution. Consequently, a biphasic drug release design was effectively accomplished over the formulation of floating bilayer tablets.